Theory of planned behaviour approach to understand pro-environmental behaviour among young green consumers in Malaysia - Ogiemwonyi, Osarodion; Harun, Amran (Brill, 2021)
The depletion of the natural environment and earth-wide natural resources have led to the increasing demand for green products. This has made young consumers carry on the green, and as a result, it affects the organization’s bottom line in building a positive image and goodwill message. This research explored the facet to investigate while applying some constructs from the Ajzen’s existing theory of planned behaviour (TPB) model with additional construct. 250 viable responses were applied and path modelling using SmartPLS 3.0 analyses was used to establish the model proposed. The results indicate that among the TPB constructs, perceived behavioural control (PBC), green perceived attitude (GPA), and other contextual constructs influence pro-environmental behaviour (PEB) positively. Looking at the relative importance of constructs, perceived green culture (PGC) followed by (GPA) had a stronger impact on PEB. The study provides evidence that young green consumers exhibit great concern towards environment, through model supportability and the inclusion of additional constructs which was supported in the TPB providing insight, and holding a sense of responsibility in the consumption pattern for a peaceful future. The obtained results can promote scientific progress in the respective research area and policy implications.